EFEKTIVITAS MIKROEMULSI-GEL SELEDRI (Apium graveolens) DALAM MENURUNKAN KADAR CALPROTECTIN GCF PADA MODEL PERIODONTITIS KRONIS - Prihastuti, Christiana Cahyani; Salisa, Ziyada; Rakhmawati, Rakhmawati; Taqwim, Ali; Satrio, Rinawati (Universitas Baiturrahmah, 2025)
Background: Calprotectin is a neutrophil secretion product that serves as one of the biomarkers for periodontal tissue inflammation. Calprotectin levels in Gingival Crevicular Fluid (GCF) are reported to increase in periodontitis conditions. Celery (Apium graveolens) contains flavonoids and polyphenols that have potential anti-inflammatory properties. The topical microemulsion-gel formulation offers optimal bioavailability of active substances when applied to periodontal pockets. Objective: To determine the effect of celery microemulsion-gel on GCF calprotectin levels in an experimental model of chronic periodontitis. Methods: This experimental study used 25 male Wistar rats (Rattus norvegicus) divided into 5 groups (n=5): healthy control group, negative control group, and three treatment groups receiving Apium graveolens microemulsion-gel at concentrations of 25%, 50%, and 100%. The chronic periodontitis model was induced using P. gingivalis. Apium graveolens microemulsion-gel (0.7 ml) was applied to the inflamed gingival sulcus for 7 days. GCF samples were collected using filter paper and calprotectin levels were measured using ELISA method. Data analysis was performed using One-Way ANOVA followed by Least Significant Difference (LSD) test. Results: GCF calprotectin levels in the Apium graveolens microemulsion-gel treatment groups were lower compared to the negative control group (p<0.05), with the lowest levels observed in the 50% concentration group. There was no significant difference between the treatment groups and the healthy control group (p>0.05). Conclusion: Apium graveolens microemulsion-gel effectively reduces GCF calprotectin levels in chronic periodontitis model, indicating an anti-inflammatory effect.